High-temperature electrochemical synthesis of carbon-containing inorganic compounds under excessive carbon dioxide pressure - Novoselova I.A.; Volkov S.V.; Oliinyk N.F.; Shapoval V.I. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Features of the electroreduction of carbon dioxide dissolved in the equimolar melt of sodium and potassium chlorides under excessive pressure of up to 1.7 MPa have been studied by cyclic voltametry over a wide polarization rate range. It has been found that the electrode process occurs in two stages at sweep rates of ≤0.1 V s-1, and its mechanism has been suggested. The cathodic product is polycrystalline graphite. Systems and conditions for producing two- and three-component refractory metal carbides using CO2 as a synthesis component have been selected.